2019
DOI: 10.1016/j.buildenv.2018.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effect of human body on cough droplets evaporation and dispersion in an enclosed space

Abstract: A B S T R A C TThis study numerically investigated the thermal effect of human body on the time-dependent dispersion of cough droplets with evaporation process. The thermal flow of human body was imitated using a 3D thermal manikin with real body features, while a recent developed multi-component Eulerian-Lagrangian approach was used to address the effects of inhomogeneous temperature and humidity fields on droplet evaporation. By comparing the results yielded without and with the human body heat, the outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 32 publications
5
77
0
Order By: Relevance
“…They report that as the relative humidity increases the extent of droplet spread decreases [18,20], yet the horizontal range of the cloud propelling the drops was found to increase with increase in relative humidity, due to the role of buoyancy of the exhaled cloud [17]. For droplets less than 20 µm in diameter, local airflow field due to body heat is an important factor in determining the extent of spread since it can lift the droplets upwards into the breathing zone [40]. Studies have also shown that depending on the flow direction and airflow pattern, increasing ventilation rate can effectively reduce the risk of long range airborne transmission [41].…”
Section: Discussionmentioning
confidence: 99%
“…They report that as the relative humidity increases the extent of droplet spread decreases [18,20], yet the horizontal range of the cloud propelling the drops was found to increase with increase in relative humidity, due to the role of buoyancy of the exhaled cloud [17]. For droplets less than 20 µm in diameter, local airflow field due to body heat is an important factor in determining the extent of spread since it can lift the droplets upwards into the breathing zone [40]. Studies have also shown that depending on the flow direction and airflow pattern, increasing ventilation rate can effectively reduce the risk of long range airborne transmission [41].…”
Section: Discussionmentioning
confidence: 99%
“…Nicas et al is cited as evidence that 99.9% of the fluid volume ejected during a cough is in large particles [3]. We believe that this should be interpreted with caution because there is also evidence suggesting that a much higher proportion of particles emitted are in the small, potentially airborne, range [2].…”
mentioning
confidence: 81%
“…There remains considerable debate about the extent to which airborne spread of SARS-CoV-2 occurs. Small droplets (< 5 lm) are thought to remain suspended in the air and could theoretically be inhaled into the lungs causing infection [2]. Loose fitting 'surgical' masks will not prevent such inhalation and only a tight-fitting filtering mask is adequate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…human, carpet, electronic devices, etc.) [4][5][6]. When contaminants are highly concentrated locally, these commonly used ventilation systems would be most likely promoting the transport of local contaminants rather than removing or isolating them away from further spreading.…”
Section: Introductionmentioning
confidence: 99%